The Effect of Ozonation on the Biodegradability of Refractory Organic Substances in Water - Stephenson, Paul (My University, 1979)
Most sources of drinking water supply contain dilute concentrations of natural and synthetic organic substances which are not readily degraded by micro-organisms. Many of these compounds are known or suspected carcinogens, and/or may act as precursors for the formation of chlorinated hydrocarbons during the chlorination disinfection processes practiced in water treatment plants. The removal of these substances prior to chlorination is therefore desirable.
The objective of this study was to test the claim that the oxidation of these organic substances by ozone results in the formation of more readily biodegradable compounds. A 25 ℓ laboratory ozone contactor was designed and built to simulate the ozonation process in a typical water treatment plant. The apparatus was used to ozonate samples of surface water and dilute synthetic aqueous solutions at applied doses ranging from 20 mg/ℓ to 40 mg/x. The biodegradability of ozonated and unozonated 10 ℓ samples was then evaluated in electrolytic respirometers, based on the changes in soluble Total Organic Carbon, Chemical Oxygen Demand, UV absorbance, and Biochemical Oxygen Uptake measurement.
The ozonation system successfully simulated full scale operating conditions, achieving greater than 90% ozone utilization. Total Organic Carbon removal was described by a first order system with reaction rate constants ranging from 0.0041 min‾¹ to 0.023 min‾¹.
Ozonation was found to improve the biodegradability of refractive organic substances in the three water sources examined. However the results show considerable variation depending on the particular source ozonated. Generally higher applied ozone doses improved biodegradability. Total Organic Carbon removal for the combined ozonation/biodegradation process ranged from 10% to 70% depending on the specific ozone dose and water source.
For oxygen uptakes less than 2 mg/ℓ the respirometry equipment provided only qualitative evidence of bacterial activity. It is recommended that further studies should evaluate the use of an electrolytic respirometer which is independent of atmospheric pressure fluctuations.
Keywords: Chemical Engineering; Chemical Engineering